Comparison of 10 noninvasive models for predicting overall survival in patients with intermediate-stage hepatocellular carcinoma. Issue 33 (20th August 2021) - Hsu, Wei-Fan; Chang, Kai-Chih; Chen, Te-Hong; Lin, Chien-Hung; Lin, Ying-Chun; Tsai, Ming-Hung; Chen, Pei-Yu; Wang, Hung-Wei; Chu, Chia-Sheng; Peng, Cheng-Yuan
Abstract : Abstract: Intermediate-stage hepatocellular carcinoma (HCC) is heterogeneous in terms of tumor size, number, and effects on liver function. Various noninvasive models have been proposed to assess functional hepatic reserve or fibrosis severity in patients with HCC. This study assessed the feasibility of 10 noninvasive models and compared their prognostic ability for patients with intermediate-stage HCC. This study retrospectively enrolled 493 patients with intermediate-stage HCC who received treatment at China Medical University Hospital from January 2012 to November 2018. Demographic data, clinical features, and factors associated with overall survival (OS) were recorded at baseline. Receiver-operating characteristic curve analysis and the DeLong method were respectively employed to evaluate and compare the models' OS prediction performance. Of the 493 patients, 373 (75.7%) were male, and 275 (55.8%) had liver cirrhosis (LC). The median age was 64 years (interquartile range: 55–72). Most patients had tumor volume ⩽50% (n = 424, 86.0%), and the maximum tumor size was 6.0 (4.0–8.5) cm. The median α-fetoprotein was 36.25 (6.13–552.91) ng/mL. The patients underwent transarterial chemoembolization (TACE, n = 349) or surgery (n = 144). The median follow-up period was 26.07 (9.77–48.27) months. Across the 10 models, the albumin–bilirubin (ALBI) score had the highest area under the receiver operating characteristic curve (AUROC) (0.644, 95% confidence interval: 0.595–0.693) in all patients. In subgroup analyses, the Lok index, platelet–albumin–bilirubin score, ALBI score, and Lok index had the highest AUROC values in patients without cirrhosis, with cirrhosis, undergoing TACE, and undergoing surgery, respectively. Multivariate Cox regression analysis revealed that independent predictors of longer OS were ALBI grade 1 in all patients, patients with LC, and patients undergoing TACE and Lok index grade 1 in patients without LC and patients undergoing surgery. Among the 10 noninvasive models, ALBI score exhibited the highest diagnostic value in predicting OS for all patients, patients with cirrhosis, and those undergoing TACE, and Lok index grade exhibited the highest diagnostic value in predicting OS in patients without cirrhosis and those undergoing surgery. Abstract : Supplemental Digital Content is available in the text